Elevated Serum Titanium Levels in Children With Early Onset Scoliosis Treated With Growth-friendly Instrumentation. Issue 6 (July 2020) - Li, Ying; Graham, Chelsea K.; Robbins, Christopher; Caird, Michelle S.; Farley, Frances A.
Abstract : Background: A previous study showed significantly higher serum titanium levels in patients with early-onset scoliosis (EOS) treated with traditional growing rods (TGR) and magnetically controlled growing rods (MCGR) compared with controls. Children with vertical expandable prosthetic titanium rib (VEPTR) were not assessed. The purpose of this study was to compare serum titanium levels in EOS patients treated with TGR, MCGR, and VEPTR. We hypothesized that EOS patients treated with all forms of growth-friendly instrumentation (GFI) have elevated serum titanium levels. Methods: This was a prospective cross-sectional case series. Serum titanium levels were collected from patients with GFI who were enrolled in an EOS database. Blood samples were collected at a clinic visit or lengthening/exchange procedure between April and December 2018. The normal range for serum titanium is 0 to 1 ng/mL. Analyses were conducted using analysis of variance and Bonferroni post hoc test. Results: A total of 23 patients (2 TGR, 8 MCGR, 13 VEPTR) were analyzed. There was a significant difference in age at the time of blood sample collection (12.5 vs. 9.8 vs. 7.5 y, P =0.015) and serum titanium level (1.5 vs. 4.5 vs. 7.6 ng/mL, P =0.021) between TGR, MCGR, and VEPTR, respectively. All of the MCGR and VEPTR patients had a serum titanium level ≥2 ng/mL. Binary comparisons showed that VEPTR had a significantly higher serum titanium level than TGR ( P =0.046). There was no difference in serum titanium level when MCGR was compared with TGR and VEPTR. Time from implant insertion to blood sample collection, number of rods currently implanted, total number of rods implanted throughout treatment, and number of lengthenings per patient was similar between the groups. Conclusions: Elevated serum titanium levels may be present in EOS patients treated with all forms of GFI. Although our TGR patients had indwelling implants for the longest period of time, they had the lowest serum titanium level. Repetitive chest wall motion during respiration may lead to continued wear and metal ion release with VEPTR. Level of Evidence: Level II—therapeutic.